Identificación y evaluación de impactos ambientales en el proceso de envasado de cloro; para la estructuración de un plan de manejo ambiental, en la planta industrial Mónica Fleury en el cantón La Maná. - Moreano Terán, Nancy Fabiola (2016)
Application of Management Systems Environmental Quality provides opportunities for continuous improvement to companies and ensure production levels; system integration in the field of health, environment and development; reduces the risk of possible accidents, proper handling and effluent emissions, improving the competitiveness of it; the application of methods and measures to control systematically from the source and nature of the emission or discharge in question, can reduce, mitigate or control environmental pollution. quantitative and qualitative methods was used for the identification and evaluation; the application of Arboleda method allowed individually evaluate the actions at different stages of the production process by evaluating parameters such as: Class, Presence, Evolution, Magnitude assigning a quantitative and qualitative environmental rating which was obtained as a result: Total Absolute negative impacts Absolute Total of 23.39 and the positive impacts of 30.77 showing a net impact of 7.37 which shows that the presence of productive activity generates a positive impact on the local strengths and negative impacts that can be controlled prevention measures from the source and method of flow chart, cause and effect matrix allowed to characterize the activities of chlorine packaging process. This research was also based on the Unified Environmental Information System (Suiá) which is a working structure that integrates environmental information in one place to generate geographical indicators, documentaries, statistics and process automation; system developed to manage procedures and projects aimed at monitoring, recording, maintenance and preservation of the environment. Such as proposed Environmental Management Plan was designed as a tool for planning, as it brings set of criteria, strategies, actions and programs that respond to business needs and environmental conservation.